PO 109 - MULTIDISCIPLINARY MANAGEMENT OF A PATIENT WITH AN OESOPHAGEAL PERFORATION BY A FOREIGN BODY - Almeida, Carolina; Carvalho, Sofia; Romão, Cristina; Guerreiro, José (Journal of the Portuguese Society of Anesthesiology, 2023)
x